Martensitic transformation in cu—sn alloys - Dhananjai P.; Ojha S.N.; Tiwari R.S. (My University, 2025)
Studies on martensitic transformation in β phase Cu-Sn alloys are reviewed with special emphasis on crystal structures, microstructure and the nature of internal defects in as-cast as well as rapidly solidified specimens. © 1991, Taylor & Francis Group, LLC. All rights reserved.